A modified gran method for determination of equivalence points in potentiometric precipitation titrations - Magallanes, Jorge Federico; Caridi, Aurora Francisca (1981)
Fil: Magallanes, Jorge Federico Comisión Nacional de Energía Atómica; Argentina